Enhanced dark fermentative hydrogen production by zero-valent iron activated carbon micro-electrolysis. (28th September 2015) - Zhang, Lei; Zhang, Lixia; Li, Daping
Abstract This paper investigated the enhancement effect of zero-valent iron activated carbon (ZVI-AC) micro-electrolysis system on fermentative hydrogen production from glucose by a mixed bacterial consortium. The results showed that addition of ZVI obtained 38.2％ more hydrogen yield, and ZVI-AC micro-electrolysis could further enhance hydrogen yield (improving rate 50.2％). The ZVI-AC also got the highest hydrogen production potential and maximum hydrogen production rate (429 ± 6.1 mL and 11.50 ± 0.74 mL/h respectively). The concentration of ferrous ion, final oxidation-reduction potential and pH were measured to understand the mechanism of enhanced hydrogen production by ZVI-AC micro-electrolysis. We concluded that ZVI-AC micro-electrolysis provided a favorable environment which was proposed to be responsible for the improvement of fermentative hydrogen production. In addition, high-throughput sequencing proved that ZVI-AC micro-electrolysis could enhance diversity of microbial community and enrich Clostridium spp. for hydrogen production.